Eliciting mental models of science and risk for disaster communication: A scoping review of methodologies. (July 2022) - Doyle, Emma E.H.; Harrison, Sara E.; Hill, Stephen R.; Williams, Matt; Paton, Douglas; Bostrom, Ann
Abstract: We present a scoping review of methods used to elicit individuals' mental models of science or risk. Developing a shared understanding of the science related to risk is crucial for diverse individuals to collaboratively manage disaster consequences. Mental models, or people's psychological representation of how the 'world works', present a valuable tool to achieve this. Potential applications range from developing effective risk communication for use in short-warning situations to community co-development of future communication protocols for the co-management of risk. A diverse range of tools, in diverse fields, have thus been developed to elicit these mental models. Forty-four articles were selected via inclusion criteria from 561 found through a systematic search. We identified a wide range of direct and indirect elicitation techniques (concept, cognitive, flow, information world, knowledge, mind, and fuzzy cognitive maps, and decision influence diagrams) and interview-based techniques. Many used multiple elicitation techniques such as free-drawing, interviews, free-listing, sorting tasks, attitudinal surveys, photograph elicitation, metaphor analysis, and mapping software. We identify several challenges when designing elicitation methods, including researcher influence, the importance of external visualization, a lack of evaluation, the role of 'experts', and ethical considerations due to the influence of the process itself. We present a preliminary typology for elicitation and analysis and suggest future research should explore methods to assess the evolution of mental models to understand how conceptualisations change through time, experience, or public education programs. These lessons have the potential to benefit both science and disaster risk communication activities, given best practice calls for mutually constructed understanding.